Pesantren, Women’s Agency and Arranged Marriages in Indonesia - Wafiroh, Nihayatul (IAIN Surakarta, 2018)
This paper is a case study based on the research of the process of arranged marriages in Pesantren. Arranged marriages have basically been a tradition in the world for a long time. In the process, the women involved in arranged marriages are often put in the position of an object and are considered to have no voice. Women have been seen as passive agents that do not contribute anything in the process of arranged marriages, whereas those who have full power in the process of arranged marriages in Pesantren are the Kyai or other male family members. This study took place in the five major Pesantren in East Java. One female informant, the daughter of a Kyai, was taken from each Pesantren so there were five informants. This research was conducted through in-depth interviews using the capital theory by Pierre Bourdieu, power relation by Michel Foucault, and women's agency by Sherry B. Ortner. This study reveals that Kyai’s daughters and wives, Nyai, are active agents, as well. Using the capital they have, women played their agencies in different ways to achieve certain goals. They engage in critiques on the habitus practice of arranged marriages. They also negotiate and resist when the arranged marriage process runs. This study confirms that doing research focused on women’s voice can expose additional aspects of women’s agency that have been widely ignored. Keywords:Pesantren, Women’s agency, Arranged marriages